Factores socioculturales, nivel de conocimiento y presencia de enfermedades diarreicas, HUAMACHUCO - Paredes Alvarez, Doris Estefani (2016)
This research study, correlational descriptive, 88 mothers sample who had their minor children 1 to 4 years with the presence of diarrheal illness in the Leoncio Prado, Huamachuco Hospital in order to determine the relationship of selected sociocultural factors and level of knowledge of mothers with the presence of acute diarrheal diseases in children 1 to 4 years. one survey form was applied, the data revealed that the incidence of acute diarrheal disease are high with 89.8%. Regarding socio-cultural factors, water is obtained in 53.4% of the well and river, excreta disposal is in a latrine (67%), there is overcrowding by 71%, 70.5% breeding animals. Regarding the level of knowledge, it was observed that 83% of mothers have an adequate level of knowledge. water supply, hygiene habits, animal husbandry and income with the presence of diarrheal diseases: statistically significant relationship between sociocultural factors was found. Keywords: acute diarrhea disease, socio-cultural factors, level of knowledge.